Knowledge, awareness, attitudes, and standard operating procedures (SOPs) towards practices for COVID-19 infection prevention in Sarawak, Malaysia - Chan, Wei Chiang; Lo, May Chiun; Abang Azlan, Mohamad; Chin, Ying Sin (AME Publishing Company, 2022)
The coronavirus disease pandemic is a viral disease that is spreading globally. In Malaysia, the government has contributed much effort in preventing the spread of the disease. However, the confirmed cases have kept increasing over the past year. Hence, there is a need to study the factors affecting the practices of the coronavirus disease prevention. A total of 1,515 datasets were collected from the respondents of 13-year-old and above within the whole Sarawak. Preliminary data analysis was performed by Statistical Package for the Social Sciences 26.0, then partial least squares structural equation modelling analysis were performed using WarpPLS 7.0 to investigate the relationship of general public knowledge, public awareness, attitude and opinions of standard operating procedures toward practices of the coronavirus disease prevention. Besides, the analysis of the responses for each of the measurement item was reported. The result indicated that general public knowledge, public attitude and opinions of standard operating procedures were significantly impacting the practices of the coronavirus disease prevention. The study further revealed that public awareness was not impacting practices of the coronavirus disease prevention. It is imperative for the government to educate the public on the coronavirus disease knowledge. Besides, the public should do their part to coordinate with the government in preventing the coronavirus disease from the spread.